Annulment Actions and the V4: Taking Legislative Conflicts Before the CJEU - Marton Varju; Veronika Czina; Katalin Cseres; Ernő Várnay (Politics and Governance, 2024)
The EU member states have been using the action for annulment to challenge the legality of EU measures while pursuing a range of non-legal and essentially political motivations. This also holds for the V4 member states, which have also resorted to annulment actions to judicialize their legislative conflicts within the EU before the CJEU. Among the V4, Poland has been the most frequent litigant, using this institutional tool increasingly actively during the last 10 years. Poland’s behavior appears to confirm expectations of differentiation among this group of member states. It also coincides with a period of political change marked by deep legislative conflicts within the EU. The V4 annulment challenges against EU legislative measures usually made a genuine effort to achieve the legal objective of annulling the challenged legal act. However, there is evidence that they also pursued certain political motivations or a combination of them. These could include the securing of gains in domestic politics, avoiding the local costs of an EU policy misfit and/or promoting a preferred policy position, and/or influencing EU competence arrangements. In a few cases, the litigant member state aimed to avoid concrete material disadvantages. Securing a legal interpretation from the CJEU that would influence the behavior of other EU actors or clarify the law affecting the position of the applicant member state also motivated some of the V4 legal challenges.